SYSTEMATIC LITERATURE REVIEW: ANALISIS MODEL RASCH PADA INSTRUMEN SELF-CONFIDENCE MATEMATIKA UNTUK SISWA SMA - Elga Putri Mishali, Aulia; Nindiasari, Hepsi; Syamsuri, Syamsuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics self-confidence is an important affective aspect influencing students’ achievement in mathematics learning. However, measuring students’ mathematics self-confidence requires valid and reliable instruments to ensure accurate measurement results. This study aimed to analyze the quality of mathematics self-confidence instruments for senior high school students using the Rasch Model. This research employed the Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework through the stages of identification, screening, eligibility, and inclusion. Article searches were conducted using Google Scholar, Scopus, and ERIC databases with the assistance of Publish or Perish and Mendeley applications. The articles were selected based on inclusion and exclusion criteria with a publication range from 2021-2025. A total of 30 articles met the criteria, consisting of 18 Sinta-indexed journals (Sinta 2-Sinta 4), 7 Scopus-indexed international journals, and 5 ERIC-indexed journals. The research subjects in the selected studies involved senior high school students aged 15-18 years from SMA, MA, and SMK levels. The findings indicated that most instruments had good psychometric quality, with items meeting the Rasch Model fit criteria, high reliability, and satisfactory unidimensionality. However, several studies still identified misfit items and incomplete Differential Item Functioning (DIF) analysis. Therefore, the Rasch Model is recommended for developing more valid and reliable mathematics self-confidence instruments for senior high school students.